أثر المحاسبة الإبداعية على جودة القوائم المالية دراسة عينة من الاكاديمين والمهنيين في مجال المحاسبة والمراجعة - عياشي, الاخضر; عياشي, عبد الله (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى ابراز الأثر الذي تخلفه كلا من الممارسات المضللة والمغالطة بالطرق القانونية والتي ينجم عنها ما يسمى بالمحاسبة الإبداعية عند معالجة البيانات المالية وتحويلها الى معلومات مالية في شكل مخرجات تدعى القوائم المالية والتي تم الاعتماد فيها على كل من المنهج الوصفي والمنهج التحليلي بالإضافة إلى منهج دراسة الحالة، وذلك عن طريق تسليط الضوء على بعض المفاهيم النظرية المتعلقة بمتغيرات الدراسة المتمثلة في كل من المحاسبة الإبداعية والقوائم المالية. ومن أجل تحقيق هذا الهدف تمت دراسة ميدانية على عينة من الأكاديميين شملت أساتذة متخصصين في مجال المحاسبة والمالية والمراجعة، والمهنيين من محافظي الحسابات والمحاسبين والتي استخدمت فيها أداة الاستبيان، وبعد تحليل وتفسير النتائج واختبار الفرضيات، توصلت الدراسة إلى مجموعة من النتائج أهمها أن المحاسبة الإبداعية هي شكل من أشكال التحايل المحاسبي والذي يمارس دون أي خرق للقوانين والمعايير المحاسبية، بحيث يؤثر سلبا على جودة القوائم المالية. The current study aims to highlight the impact of both misleading and deceptive practices via legal methods. It is resulted in the so-called creative accounting when processing financial data and transforming it into financial information in the form of outputs called financial statements, which have been relied on both the descriptive approach and the analytical approach. Thecase study, by shedding light on some theoretical concepts related to the study variables represented in both creative accounting and financial statements. In order to achieve this goal, an actual study was conducted on a sample of academics, including lecturers specialized in the field of accounting, finance and auditing, and professionals from accountants and accountanting, in which the questionnaire was used. The stuy found that creative accounting is a form of accounting fraud that is practiced without any violation of accounting laws and standards, as this type of practice negatively affects the quality of the financial statements.
The impact of creative accounting on the quality of financial statements A field study for a sample of academics and professionals in the field of accounting and auditing
مقال
Keywords: محاسبة إبداعية ; معلومات محاسبية ; قوائم مالية ; جودة معلومات محاسبية ; خصائص نوعية